Solventless Lactam Synthesis by Intramolecular Cyclizations of α-Iminoester Derivatives under Microwave Irradiation - Aicha Derdour; Jack Hamelin; Fatima-Zohra Zradni (Molecules, 2007)
We have previously reported a new synthesis of amides from esters and amines under microwave irradiation, offering much higher yields than those achieved with conventional heating [1]. We have now extended these studies to the ring closure of neat iminoesters I2, I3 and I4-I6 to give five- and six-membered ring lactams L5, L6 and larger lactams L7-L9 (where I means imine and L means lactam), respectively, under both classical heating conditions and microwave irradiation.